Prospect of secondary agriculture in enhancing farmers’ income - Singh, Rajbir; Mann, Sandeep; Mittal, Sachin (Indian Farming, 2021)
Secondary agriculture is basically entrepreneurship development method that helps in generating income and employment for farming household in village areas. To achieve the objective of sustainable development and doubling farmers’ income, implementation of different enterprises under secondary agriculture is most necessary. It is the complement of primary agriculture operations at farm level. Through secondary agriculture, money can flow from urban areas to rural areas, that helps in development of rural households. The broad categorization of secondary agriculture under enterprises is required to be managed effectively. These enterprises help in increasing the income of the farmers by 30-40%. As the demand of nutraceuticals and value-added products is increasing in the market, there is immense scope of secondary agriculture in the country. However, new policies and initiatives for encouraging value-addition of the agricultural produce in production catchment areas are required.